2021
DOI: 10.1021/jacs.1c06186
|View full text |Cite
|
Sign up to set email alerts
|

Aza-Matteson Reactions via Controlled Mono- and Double-Methylene Insertions into Nitrogen–Boron Bonds

Abstract: Boron-homologation reactions represent an efficient and programmable approach to prepare alkylboronates, which are valuable and versatile synthetic intermediates. The typical boron-homologation reaction, also known as the Matteson reaction, involves formal carbenoid insertions into C−B bonds. Here we report the development of aza-Matteson reactions via carbenoid insertions into the N−B bonds of aminoboranes. By changing the leaving groups of the carbenoids and altering Lewis acid activators, selective mono-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
5
22
0
Order By: Relevance
“…20 Characterization data for compounds 1l-p were in accordance with those in the literature. 13 Characterization data for compound 1c was in accordance with that found in the literature. 31 Synthesis of novel aminoboranes.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…20 Characterization data for compounds 1l-p were in accordance with those in the literature. 13 Characterization data for compound 1c was in accordance with that found in the literature. 31 Synthesis of novel aminoboranes.…”
Section: Methodssupporting
confidence: 87%
“…12 More recently, Dong et al reported aza-Matteson reactions using aminoboranes in conjunction with n BuLi as an ionic Lewis base activator (Figure 1c). 13 Due to the need for strong LAs or strong ionic Lewis bases, these methods cannot be broadly applied in organic synthesis. Despite these limitations, the abovementioned reports demonstrate the significant potential of ambiphilic aminoboranes 14 to serve as reagents for the rapid construction of nitrogen-containing organic molecules decorated with synthetically valuable boryl groups 15 from feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, N -borylamines, the initial products of deoxygenation of isocyanates with HBPin, can be directly used in C–N bond formation reactions, opening up one-pot synthetic routes to more complex N-containing organic products. 35…”
Section: Resultsmentioning
confidence: 99%
“…First, the reaction may proceed via a reaction between the ynone 1a and aminoborane A in situ generated from dimethylamine 2a and pinacolborane. 15 The aminoborane coordinates with ynone 1a through intermediate B and subsequently gets reduced to complex- C (Path-I). 16 On the other hand, it also possibly undergoes a Michael addition process to generate the hydroamination product enaminone 3aa′ (Path-II).…”
mentioning
confidence: 99%